682 Cardioncology: is it time to spread the need for dedicated management?. (8th December 2021) - Magnesa, Michele; Casavecchia, Grazia; Barone, Roberta; Riccardo, Mariolina; Corbo, Delia; Brunetti, Natale Daniele
Abstract: Case report: A 56-year-old man affected by micromolecular multiple myeloma was treated by several cycles of different chemotherapy drugs from September 2015 to December 2020. The chemotherapy regimen included 4-cycle first-line therapy with Bortezomib, Thalidomide, and Dexamethasone; 19-cycle second-line therapy with Carfilzomib, Revlimid, and Dexamethasone; 8-cycle third-line therapy with Daratumumab, Revlimid, and Dexamethasone; finally, he was started on therapy with Pomalidomide and Endoxan. During the various treatments, the patient did not follow a dedicated cardiological follow-up programme. In November 2020, he was hospitalized in the Intensive Care Unit for acute pulmonary oedema and subsequently discharged with a diagnosis of mild left ventricular systolic dysfunction (LVEF 50%). One month later, due to the worsening of dyspnoea, the patient was finally referred to our Cardioncology Unit for the medical assessment. The echocardiographic examination revealed a global and severe left ventricular dysfunction (FE 40%) with significant reduction in left ventricular global longitudinal strain (GLS −10%). For these reasons, we referred the patient to coronary angiography. Conclusions: This case report wants to underline how important a dedicated cardiological follow-up is in patients undergoing chemotherapy drugs, especially if used at high doses and for many cycles.